СОЦИАЛЬНО-КОГНИТИВНЫЕ ОСОБЕННОСТИ ИССЛЕДОВАНИЙ ДЕЛОВОГО ДИСКУРСА (TAMADDUN NURI JURNALI, 2024)
This article argues that business discourse is a multifaceted area requiring extensive research. It also examines the socio-cognitive features of business discourse and their linguistic and cultural interpretations. The study explores how speech acts in business communication are shaped by various cultural and social contexts, the cognitive processes between communicators, shared knowledge, and social norms. Based on the research of T.A. van Dijk and other scholars, the cognitive model of business discourse and its connection to social contexts are discussed. The analysis focuses on how cultural and social parameters influence the formation of business relationships during communication and the significance of the socio-cognitive approach in studying business discourse.